A formação continuada realizada pelo coordenador pedagógico nas escolas públicas municipais de tempo integral de Ponta Grossa-PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The potential thesis belongs to the teaching and learning research line and presents as the object of research the continuous training carried out by the pedagogical coordinator in the municipal public schools of ponta grossa - PR. As a guide question of the project, it is asked: How are continuing formations developed by the pedagogical coordinator in the full-time municipal public schools of Ponta Grossa - PR? As a general objective, it is delimited: To analyze the continued training performed by pedagogical coordinators in the municipal public schools of full-time of Ponta Grossa - PR. The specific objectives are: a) To understand the effects of the partnership with the Lemann Foundation on the continuing education carried out by the pedagogical coordinator in the municipal public schools of Ponta Grossa - PR; b) Identify the characteristics of continuing education performed by the pedagogical coordinator in the municipal public schools full-time of Ponta Grossa - PR. The pedagogical coordinator is understood as an integral part of the body of teachers who perform so work in the coordination and pedagogical organization of the school. Among the attributions that are incumbent upon him, we highlight the activities that involve the continuous training of teachers and mediation for the construction and collective implementation of the Political Pedagogical Project (PPP), among other actions that aim at learning students. In the case of this research, when alludes to continuing education, it is referring to the spaces-times that the pedagogical coordinator organizes in favor of the professional development of teachers who work in the school. Thus, continuing education is a planned, intentional proposal that takes place collectively with the group of teachers within the school, and can enable, together with other elements, a new meaning to pedagogical practice, as well as an ally in the reconfiguration of the organization of pedagogical work. In this sense, the importance of the pedagogical coordinator's work as the holder of a specific knowledge that gives him legitimacy to organize, plan and implement continuing education within the school is defended. The methodological theoretical framework of this study was based on Pierre Bourdieu (1983, 1996, 1998, 2004, 2009, 2003, 2014), Ball (2005, 2006, 2020), Freitas (2005, 2007, 2013, 2018), Giroux (1987, 1997) and Brzezinski (1996, 1999). Also, authors who deal with the continuing education carried out by the pedagogical coordinator: Placco (2003), Domingues (2014), Nóvoa (1995) and Imbernón (2009, 2010). The field of research is the full-time municipal public schools of Ponta Grossa - PR; the participants of the research are the pedagogical coordinators and the teachers of the municipal public schools full-time in Ponta Grossa - PR. The methodological approach is qualitative and, for data collection and production, we opted for questionnaires and semistructured interviews with pedagogical coordinators and teachers. For data analysis, we opted for Discursive Textual Analysis (ATD), which is characterized as a data analysis approach that transitions between two forms of qualitative research analysis (content analysis and discourse analysis (MORAES; GALIAZZI, 2006). The results of this research indicate that the management carried out in full-time municipal public schools in Ponta Grossa - PR is the effect of a broad corporate project, which aims to adapt education to the new standards of international competitiveness and economic resizing. The new possibilities of governance, with the restructuring of the State, seek to guarantee neoliberal supremacy at a global and local level, and it is in this sense that privatization is strengthened in social areas, strategically submitting educational principles to the logic of the market. Therefore, it is argued that the continuing education that is developed by the pedagogical coordinator in full-time municipal public schools in Ponta Grossa - PR has in itself a prescriptive, normative character, limited to technical competences that aim to produce a they aim to produce a teaching behavior based on the accountability of the teachers and pedagogical coordinators.
Keywords: Coordenador pedagógico; Formação continuada; Relação público-privado; Pedagogical coordinator; Continuing training; Public-private relationship; CNPQ::CIENCIAS HUMANAS::EDUCACAO